Cometary science after Rosetta. (13th July 2017) - Jones, Geraint H.; Knight, Matthew M.; Fitzsimmons, Alan; Taylor, Matt G. G. T.
Abstract : The European Space Agency's Rosetta mission ended operations on 30 September 2016 having spent over 2 years in close proximity to its target comet, 67P/Churyumov–Gerasimenko. Shortly before this, in summer 2016, a discussion meeting was held to examine how the results of the mission could be framed in terms of cometary and solar system science in general. This paper provides a brief history of the Rosetta mission, and gives an overview of the meeting and the contents of this associated special issue. This article is part of the themed issue 'Cometary science after Rosetta'.